Experience (Mostly Negative) with the Use of Sympathomimetic Agents for Weight Loss - Mario A. Inchiosa (Hindawi Limited, 2011)
Sympathomimetic agents have a poor history of long-term success in the treatment of obesity. From earlier experiences with amphetamine and its analogs, to more recent drugs with direct effects on adrenergic receptors or indirect effects from release of catecholamines or inhibition of reuptake, cardiovascular toxicity (strokes and cardiac arrhythmias) has been the major concern. These concerns also extended to food supplements containing ephedra alkaloids and may require consideration for current supplements containing the sympathomimetic drug, synephrine.